Business modeling of the digital platform Dérmo express Basharati for dermatologic consultations in Algeria - Lachkhem Dounia; Farhat Ahmida (جامعة عمار ثليجي, 2023)
This study aims to provide a business plan, for the project of establishing a virtual consultation platform in Algeria and the possibility of its success Where the business plan represents the first steps on the way to achieving a successful project with economic and financial returns, and to reach this. The goal It was necessary first to shed light on the general concepts about the business plan and its components, as well as its importance in relation to the various the parties involved to understand the importance of the project and the requirements for its success. In this chapter, we also touched on the components of the business plan Based on the organizational and legal scheme, to give the project a legal character, then the production and marketing scheme to search for The equipment needed by the project, as well as the methods by which the target audience can be reached to the planned To study the costs and revenues of the project, as well as the various financial aspects associated with it, which would increase the degree of certainty and reduce the risk. After analyzing and studying the business plan for the BASHARATI platform project, it was found that it is an innovation that combines the medical field with that of technology. The application offers reliable, useful information and a quality service to respond in the most efficient way to the needs of users. And it is an economically feasible project. It is possible to take advantage of its growth and expand it to achieve significant financial profits, as well as contribute to economic development.